ISOLASI DAN KARAKTERISASI BAKTERI PENDENITRIFIKASI YANG DIISOLASI DARI LUMPUR KAWASAN MANGROVE - Triyanto Triyanto; Alim Isnansetyo; Irfan D. Prijambada; Jaka Widada; Duranta D. Kembaren (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The aim of this research is to isolate denitrifying bacteria which have the highest activity to reduce nitrate. The sources of the denitrifying bacteria were mangrove sediment collected from Cilacap Regency, Central Java and Indramayu Regency, West Java. Basalt medium containing KNO3 as a source of nitrogen was used for isolating the denitrifying bacteria. Double layer agar was used for making anaerob condition. Fourty-one isolates were obtained at the first step of the isolation, 29 of them have nitrate reduction activity at a range of 0.77-95.62%. Three isolates, i.e. D19.2, DR2.1 and D27.3 having the highest activity were selected for further examination. The selected isolates were characterized and identified. Characterization includes colony and cell morphology, Gram staining, motility, spore staining and biochemical tests as catalase and oxidase. Identification was done by using profile matching to Bergey’s Manual of Determinative Bacteriology. The results indicate that isolate D19.2 and D27.3 have similarities to the characters of genus Listeria, whereas isolate DR2.1 has similarities to the characters of genus Propionibacterium. All of the selected isolates were able to grow in a medium having NaCl concentration at a range of 0.5-3.5% and pH range of 5-8. Observation of nitrate reduction ability of the isolates during five days incubation shows that isolate DR2.1 has the highest denitrifying activity. The selected isolates can be used as bioremediation agents for controlling nitrate pollution in brackish water pond.